KEPEMIMPINAN MULTIKULTURAL KEPALA SEKOLAH DALAM MENUMBUHKAN KARAKTER TOLERANSI SISWA - Puji Rinawati; Yulius Mataputun; Diki Kurniawan; Kusdianto Kusdianto; Ida M. Hutabarat; Urip Wahyudin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to analyze the principal's multicultural leadership in fostering student tolerance character through eight strategic dimensions: developing democratic attitudes, diversity paradigms, ethnic anti-discrimination, gender sensitivity, social concern, intracurricular integration, supporting/inhibiting factors, and the impacts of such leadership. This research employed a qualitative approach with a case study design at SMPIT Qurrota A’yun Abepura, Jayapura City, Papua Province. Data were collected through in-depth interviews, participatory observation, and documentation from 15 key informants, including school leaders, teachers, students, parents, and community figures. Data validity was ensured through source, technique, and time triangulation. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The results indicate that the principal successfully built a democratic climate through staff involvement in policy-making and synchronizing Islam Wasathiyah values with Papuan local wisdom. Anti-discrimination strategies and gender sensitivity were realized through fair policies regardless of ethnicity or gender. Social concern was internalized through real experiences such as the